Online Customer Behavior: An Analysis of the Effects of Cognitive and Affective Trust - Foroutan, Reza A.; Sarokolaei, Mahmoud Gholami; Rezaeian, Javad (Current Chinese Science, 2022)
Background: Although many scholars have argued that the key factor for success in the e-commerce is the deployment of a trusted and reliable process for the buyer, the meaning of customer trust in e-commerce and the factors affecting it are not still well-known and to be investigated. Understanding how customers build their trust and developing a trust model is beneficial to increase the ability to do so. Objective: The aim of this study was to investigate whether the factors such as cognitive and affective trust can affect customer behavior in online shopping or not. Methods: Questionnaire was used to collect data and to check their normality, and the Kolmogorov– Smirnov test was applied. Cronbach’s alpha was employed to test the reliability, and the Structural Equation Model (SEM) was utilized to confirm or reject the hypotheses. Inferential statistical analysis was performed using SmartPLS software. Results: While perceived website quality can affect cognitive trust, variables like security and privacies policy, and shared value of a website can influence affective trust. In addition, there are variables like prior-interaction experience, and perceived reputation of an e-tail which can impact on both cognitive and affective trust. On the other hand, it was shown that both cognitive and affective trust can influence customer satisfaction; a variable which along with internet usage experience, and online shopping experience affect loyalty intention. Conclusion: The empirical results show that cognitive and affective trust are prominent variables in online retailing. They mediate between PWQ, SPP, PIE, PETR, and SV on the one hand and CS on the other hand. In addition, CS influences LI. The same is true for OSE and IE.
Keywords: Online shopping